Perhitungan Premi dengan Asumsi Waktu Antar Klaim Berdistribusi Eksponensial - Zuharioh, Faihatuz (Matematika dan Statistika serta Aplikasinya, 2014)
In this paper, will searched how the insurance premium calculation equations assuming exponential distribution of time between the claim and the amount of claims Beta distribution. To obtain or seek the distribution of sum claims, first known form of the distribution of Ti. Because Ti valuable and continuous positive, meaning it can be assumed that the distribution of Ti is continuous and non-negative. In this paper, it is assumed that the Ti distribution is exponential. The function of the amount of the premium that is obtained by assuming an exponential and the amount